2016
DOI: 10.1589/jpts.28.46
|View full text |Cite
|
Sign up to set email alerts
|

The effects of self-mobilization techniques for the sciatic nerves on physical functions and health of low back pain patients with lower limb radiating pain

Abstract: [Purpose] This study aimed to examine the effects of self-mobilization techniques for the sciatic nerves on the quality of life in patients with chronic low back pain in the lower limbs accompanied by radiating pain. [Subjects and Methods] The subjects were divided into two groups: a group receiving of lumbar segmental stabilization exercise training including sciatic nerve mobilization techniques, which included 8 males and 7 females, and a group receiving lumbar segmental stabilization exercise training, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…For the disorder index of lower back pain, the short period of hamstring stretches for patients with lower back pain significantly decreased the index 35 ) . The self-execution of nerve mobilization for patients with lower back pain promoted the recovery of nervous tissue by stimulating soft tissues, which increased the adaptability of nerves and decreased the sensitivity, thus alleviating the symptom 36 ) . In this study, both the hamstring stretching group and nerve mobilization group showed improvement after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…For the disorder index of lower back pain, the short period of hamstring stretches for patients with lower back pain significantly decreased the index 35 ) . The self-execution of nerve mobilization for patients with lower back pain promoted the recovery of nervous tissue by stimulating soft tissues, which increased the adaptability of nerves and decreased the sensitivity, thus alleviating the symptom 36 ) . In this study, both the hamstring stretching group and nerve mobilization group showed improvement after the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The type of neural mobilisation technique and dosage varied amongst groups. The techniques used included slump (Ali et al 2015 ; Cleland et al 2006 ; Jain et al 2012 ; Jeong et al 2016 ; Karthikeyan, Jothikaran & Kiran 2014 ; Kirthika et al 2016 ; Malik, Kataria & Sachdev 2012 ; Nagrale et al 2012 ; Patel 2014 ; Rezk-Allah, Shehata & Gharib 2011 ; Tambekar et al 2015 ; Waleed 2015 ), SLR (Adel 2011 ; Ahmed et al 2013 ; Kaur & Sharma 2011 ; Malik et al 2012 ; Rezk-Allah et al 2011 ; Waleed 2015 ), bent leg raise mobilisation (Dwornik et al 2009 ; Patel 2014 ; Tambekar et al 2015 ) and neural mobilisations in side lying (Colakovic & Avdic 2013 ; Ferreira et al 2016 ; Lee & Kim 2017 ). One study reported a neural slider technique of the sciatic nerve involving the hip, knee and foot (Plaza-Manzano et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The neural mobilisation interventions were a standalone treatment in six studies (Dwornik et al 2009 ; Kaur & Sharma 2011 ; Lee & Kim 2017 ; Patel 2014 ; Tambekar et al 2015 ; Waleed 2015 ) and were combined with exercise programmes in 15 studies (Adel 2011 ; Ahmed et al 2013 ; Ali et al 2015 ; Cleland et al 2006 ; Colakovic & Avdic 2013 ; Ferreira et al 2016 ; Jain et al 2012 ; Jeong et al 2016 ; Karthikeyan et al 2014 ; Kirthika et al 2016 ; Malik et al 2012 ; Nagrale et al 2012 ; Plaza-Manzano et al 2020 ; Rezk-Allah et al 2011 ; Sharma & Sheth 2017 ). The control groups were diverse, including lumbar stabilisation, lumbar mobility exercises, hamstring stretching, advice, physical modalities or a combination treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in line with previous studies which reported that neural mobilization techniques improved pain and function in patients with nerve related low back pain. 1,1517 Additionally, neural mobilization has been reported as a superior post-surgical intervention compared with myofascial release and lumbar stabilization exercises alone in improving pain and functional disability after lumbar spinal fusion. 18…”
Section: Discussionmentioning
confidence: 99%